MAHASISWA MENGABDI : MEMAJUKAN PENDIDIKAN, KESEHATAN, DAN EKONOMI DESA MARGALUYU - Dzahira Shofa, Annisa; Riska Maulidya, Muhammad Rizwan, Cepi Awaludin; Greyven Waldo Paulus Simangunsong, M.pr Alfiqri; Putri Kenza Efrillia, Deti Damayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Community service through Real Work Lecture (KKN) is a manifestation of the Tri Dharma of Higher Education. This activity was carried out by students of Nusa Putra University in Warudoyong Hamlet, Margaluyu Village, from February to March 2025. The location of the activity was chosen because it faced various challenges in the education, health, and economic sectors. The aim of this program is to improve the quality of life of the community through empowerment in these three sectors. The method applied is field research with a descriptive qualitative approach. Data collection techniques were carried out by means of observation, interviews, documentation, and literature studies. The results of the study showed that KKN activities had a positive effect on increasing awareness of the importance of education, preventing stunting through integrated health posts and PMT, and strengthening MSMEs through branding training and product promotion. Active community involvement in this program is a key factor in the success of the activity and shows the potential for sustainable development based on collaboration.